Histotopographic characteristics of the pancreatoduodenal organocomplex in fetuses and newborns - Slobodian O.M. (Морфологія, 2008)
The object of the research was to establish a chronological order of the histotopography of the duodenum and pancreas during the perinatal period of ontogenesis. It has been established that the histostructure of the duodenal wall in early fetuses (4-5 months) is characterized by the availability of primary crypts, the muscular layer of the mucous tunic, variable thickness of the layers of the muscular coat and a feebly marked character of the serous tunic; in late fetuses (8-10 months) - by the forming of the villi of the mucous membrane, the presence of transparent goblet cells, Brunner’s glands in the submucous layer and an almost uniform thickness of the layers in the muscular tunic. The lobular structure of the pancreas becomes formed starting with the 5th-6th months of development. Goblet cells occur in the mucous tunic of the interlobular ducts and the main pancreatic duct in late fetuses and newborns. The islets of Langerhans in early fetuses make up 1.2-3.5% of the volume of the glandular component of the organ and distributed unevenly, 4.8-8.3% with a uniform distribution in late fetuses and newborns.